(untitled) (Fiep Bulletin - online, 2013)
This research aims to assess the body composition of athletes in high-level specifically in the case of professional indoor soccer in Exeter, PR. Delineate a map with the whole process be developed in the initial evaluation (pre-season), prescription and periodization of training is mainly linked to the performance of athletes, is of fundamental importance to assess the work that will be held throughout the race. The purpose of this study is to analyze at the end of the season, if there was an evolution of anthropometric profile of athletes, and if the work done with these athletes during the competition reached the expected results in terms of competition. The stages of evaluation aimed at the period of competition and will correlate the periods of pre-season with a season-high, indicating a possible difference in body composition of these athletes for two periods, so if professional athletes use of indoor soccer training sports periodizado and pre-prepared, then we subjects with different body composition profile throughout the race. The sample will be comprised of 10 individuals, male, aged between 19 and 30 years, all professional athletes to indoor soccer. The data will be collected from skinfolds at the beginning of the pre-season and the seasonhigh in January and June of 2008, using the Protocol & JACKSON POLLOCK (for male athletes), 7 folds.